Pengaruh Motivasi dan Kemampuan Menulis Karya Tulis Ilmiah terhadap Penyelesaian Skripsi Tepat Waktu Mahasiswa Akuntansi Universitas Negeri Padang - Felsi, Monica; Syofyan, Efrizal (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to determine and analyze the influence of motivation and ability to write scientific papers on the timely completion of theses of accounting students at Universitas Negeri Padang. The research population is all accounting students who have completed their thesis course and graduated at the Faculty of Economics and Business, Universitas Negeri Padang. The sample selection used the simple random sampling method. The research sample was 153 accounting students. The data analysis technique in this study was using multiple linear regression analysis. Based on hypothesis testing, it can be concluded that the motivation variable has a positive and significant effect on the timely completion of theses of accounting students. The variable of the ability to write scientific papers has a positive and significant effect on the timely completion of theses of accounting students. The variables of motivation and the ability to write scientific papers together or simultaneously have a significant effect on the timely completion of theses of accounting students. The magnitude of the influence of the variables of motivation and the ability to write scientific papers together or as a whole on the variable of timely completion of thesis by accounting students is 19.2%, while the remaining 80.8% is influenced by other variables that are not used or are outside the model used.